The Effect of The Electromagnetic Field Intensity and Duration of Time on Some of The Morphological Characteristics of The Plant Safflower Carthamus tinctorius L. - Z. Faysal, Mahir; Q. AL-obeidy, Marwa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was carried out in the field of botanical garden belonging to the Department of Biology Sciences, College of Education for Pure Science -Ibn AL-Haitham ,Baghdad University. for the growing season. 2014 -2013 to study the effect of the electromagnetic field which included five different intensities (0,5,10,15,20) MT and three periods of time, namely, (1,2,3) an hour and their interaction on some of the morphological characteristics of the safflower plant . designed experiment by Randomized Complete Block Design (RCBD) and three replicates per treatment, compared to the average using less significant difference at the level of probability (0.05) , the results showed the following:- 1-Exposing seeds to different electromagnetic field intensities led to a significant increase except the number of vegetative branches, as it gave the highest rates in the percentage of seed germination, plant height, the size of the root, leaf area and leaf area guide. The highest increase was when the seeds which were exposed to the intensity of the electromagnetic field 10MT. 2-Exposing the seeds to different time periods of the electromagnetic field led to obtain a significant increase in most of the treatment mentioned except the character of vegetable branches number and the size of root, and the highest increase when the seeds exposing for two hours for most of the qualities mentioned and for three hours to the percentage of seed germination. 3-The interaction between the factors of the study had significant effect on all treatment with the superiority of treatment 10MT for two hours to give them the best rates for the studied traits compared with the control plants.